Negative Interest Rate Risk. Atavism or Normalization of Central Banks’ Monetary Policy - Pyka, Irena; Nocoń, Aleksandra (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
In the face of the global financial crisis, central banks have used unconventional monetary policy instruments. Firstly, they implemented the interest rate policy, lowering base interest rates to a very low (almost zero) level. However, in the following years they did not undertake normalizing activities. The macroeconomic environment required further initiatives. For the first time in history, central banks have adopted Negative Interest Rate Policy (NIRP). The main aim of the study is to explore the risk accompanying the negative interest rate policy, aiming at identifying channels and consequences of its impact on the economy. The study verifies the research hypothesis stating that the risk of negative interest rates, so far unrecognized in Theory of Interest Rate, is a consequence of low effectiveness of monetary policy normalization and may adopt systemic nature, by influencing – through different channels – the financial stability and growth dynamics of the modern world economy.